Association between the oxidative balance score and preserved ratio impaired spirometry in US adults: NHANES 2007–2012 - Gu, Shengyuan; Du, Xinchao; Gu, Xiaoxia (Frontiers in Nutrition, 2025)
Background and aimsThe relationship between oxidative stress (OS) and preserved ratio impaired spirometry (PRISm) remains unclear. We aimed to utilize the oxidation balance score (OBS), a validated instrument for assessing the overall OS status, to investigate the association between OBS and PRISm.MethodsWe included data from 7,180 participants in the National Health and Nutrition Examination Survey (NHANES). The OBS was calculated using 20 components of diet and lifestyle. Binary logistic regression analyses were conducted to investigate the association between OBS and PRISm. Subsequent analyses were performed for non-smokers and smokers across different OBS levels.ResultsOBS was inversely associated with PRISm in all models (all p-values < 0.001). In subsequent analyses, the odds ratio (OR) for PRISm increased sequentially from non-smokers with high OBS, to non-smokers with low OBS, to smokers with high OBS, and to smokers with low OBS (dose–response p-values in all models ≤ 0.003); smokers with low OBS exhibited the highest PRISm incidence in the fully adjusted model (OR = 1.83, 95% CI = 1.27–2.64, p = 0.001).ConclusionA lower OBS was associated with an increased incidence of PRISm, particularly among smokers, suggesting that OS may play a pivotal role in this relationship.